Risk-Sensitive Stochastic Control and Games - Golui, Subrata (My University, 2023)
This thesis considers risk-sensitive stochastic control and game problems on countable/Borel state space for discrete/continuous-time Markov decision processes (MDPs) under certain Lyapunov conditions. Here, infinite horizon control/game problems are analyzed with various cost criteria. The controllers can take action in discrete/continuous time from their admissible strategies.
Pal, Chandan
Keywords: Markov Decision Processes; Risk-sensitive Stochastic Control; Rrisk-sensitive Stochastic Game; Zero-sum Game; Nonzero-Sum Game; Saddle Point Equilibrium; Nash Equilibrium; Discounted Problems; Ergodic Problems